The territory of colonialism. Issue 2 (3rd April 2017) - Kearns, Gerry
ABSTRACT: The territory of colonialism. Territory, Politics, Governance . Stuart Elden writes of territory as a specific form of sovereignty, and has provided its genealogy through a study of European texts. These texts drew upon a Roman legacy and engaged the practical issue of the relations between papal and monarchical powers. This paper argues that colonialism was at least as important a context for the elaboration of territory as a strategy of sovereignty. Furthermore, and as the example of Ireland shows, this colonial practice was not only a matter external to Europe.